Fatalities in High School and College Football Players. (May 2013) - Boden, Barry P.; Breit, Ilan; Beachler, Jason A.; Williams, Aaron; Mueller, Frederick O.
Background: Fatalities in football are rare but tragic events. Purpose: The purpose was to describe the causes of fatalities in high school and college football players and potentially provide preventive strategies. Study Design: Descriptive epidemiology study. Methods: We reviewed the 243 football fatalities reported to the National Center for Catastrophic Sports Injury Research from July 1990 through June 2010. Results: Football fatalities averaged 12.2 per year, or 1 per 100, 000 participants. There were 164 indirect (systemic) fatalities (average, 8.2 annually [or 0.7 per 100, 000 participants]) and 79 direct (traumatic) fatalities (average, 4.0 annually [or 0.3 per 100, 000 participants]). Indirect fatalities were 2.1 times more common than direct fatalities. The risk of a fatality in college compared with high school football players was 2.8 (95% CI, 0.7-8.2) times higher for all fatalities, 3.6 (95% CI, 2.5-5.3) times higher for indirect events, 1.4 (95% CI, 0.6-3.0) times higher for direct injuries, 3.8 (95% CI, 1.8-8.3) times higher for heat illness, and 66 (95% CI, 14.4-308) times higher for sickle cell trait (SCT) fatalities. Most indirect events occurred in practice sessions; preseason practices and intense conditioning sessions were vulnerable periods for athletes to develop heat illness or SCT fatalities, respectively. In contrast, most brain fatalities occurred during games. The odds of a fatality during the second decade, compared with the first decade of the study, were 9.7 (95% CI, 1.2-75.9) for SCT, 1.5 (95% CI, 0.8-2.9) for heat illness, 1.1 (95% CI, 0.8-1.7) for cardiac fatalities, and 0.7 (95% CI, 0.4-1.2) for brain fatalities. The most common causes of fatalities were cardiac failure (n = 100, 41.2%), brain injury (n = 62, 25.5%), heat illness (n = 38, 15.6%), SCT (n = 11, 4.5%), asthma and commotio cordis (n = 7 each, 2.9% each), embolism/blood clot (n = 5, 2.1%), cervical fracture (n = 4, 1.7%), and intra-abdominal injury, infection, and lightning (n = 3, 1.2% each). Conclusion: High school and college football have approximately 12 fatalities annually with indirect systemic causes being twice as common as direct blunt trauma. The most common causes are cardiac failure, brain injury, and heat illness. The incidence of fatalities is much higher at the college level for most injuries other than brain injuries, which were only slightly more common at the college level. The risk of SCT, heat-related, and cardiac deaths increased during the second decade of the study, indicating these conditions require a greater emphasis on diagnosis, treatment, and prevention.